Zur Synonymie der Borkenkäfer, XIII (Coleoptera: Scolytidae). 222. Beitrag zur Morphologie und Systematik der Scolytoidea). - Schedl, Karl Eduard (Contributions to Entomology = Beiträge zur Entomologie, 1963)
There are given some additional notes and corrections concerning three recently publihed papers of F. G. Browne on the Scolytidae in connection with the author's work in preparing a new edition of the respective volume of the "Genera Insectorum". Nomenclatural Actsquadridens Brown, 1960 (Diacavus), syn. n. of Diacavus philippinensis Schedl, 1942babai (Murayama, 1961) (Poecilips), comb. n. hitherto Thamnurgus babai Murayama, 1961Premnophilus Brown, 1962 (Scolytidae), syn. n. of Xyleborus Eichhoff, 1864Pseudoacacicis Schedl, 1963 (Scolytidae), gen. n.parvus Brown, 1960 (Trachyostus), syn. n. of Platypus saltator Schedl, 1935taunayi Eggers, 1928 (Xylechinus), syn. n. of Xylechinosomus contractus (Chapuis, 1869)